Aluminum oxide filled phenolic resin copper-clad plate and preparation method thereof

By adding alumina filler and modified phenolic resin to the phenolic resin, alumina filled phenolic resin copper clad plate was prepared, which solved the problems of reduced performance and insufficient flame retardant performance of copper clad plates in the prior art under high temperature environments, and achieved higher high temperature resistance and flame retardant properties.

CN119798917AInactive Publication Date: 2025-04-11JIANG SU YAO HONG ELECTRONICS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510045469.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing phenolic resin copper clad plates have reduced performance in high temperature environments and lack flame retardant performance, making it difficult to meet the high temperature resistance and safety requirements of electronic equipment.

Method used

Alumina filled phenolic resin copper clad plate was prepared by adding alumina filler and a modified phenolic resin to the phenolic resin. The method includes mixing the phenolic resin prepolymer with an alumina filler and laminated to form a copper clad plate with improved high temperature resistance and flame retardant properties.

Benefits of technology

It improves the high temperature resistance and flame retardant properties of copper clad plate, and enhances its stability and safety in high temperature and fire environments.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of copper-clad plate preparation, in particular to an aluminum oxide filled phenolic resin copper-clad plate and a preparation method thereof. The preparation method comprises the following steps: mixing a phenolic resin prepolymer, a benzenesulfonic acid prepolymer and ethanol to obtain phenolic resin microspheres; n, N-dimethylacetamide, 4-nitrophthalonitrile, the phenolic resin microspheres and anhydrous potassium carbonate are mixed, and the modified phenolic resin is obtained. The preparation method comprises the following steps: mixing modified phenolic resin, unsaturated polyester resin, butanone, modified aluminum oxide filler, a flame retardant and a photoinitiator to obtain a mixture, dipping glass fabric in the mixture, and curing at high temperature and under ultraviolet light to obtain a prepreg; and laminating the prepreg with a copper foil, and carrying out lamination molding to obtain a finished product. The finished product prepared by the preparation method has good flame retardance and high temperature resistance, so that the preparation method has a wide application prospect in the technical field of copper-clad plate preparation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of copper clad laminate preparation, in particular to an alumina filled phenolic resin copper clad laminate and a preparation method thereof. Background Art

[0002] Copper clad laminate is a composite material with a thin copper layer plated on the surface of the substrate. It has important value in the modern electronics industry and is mainly used in the fields of electronic equipment manufacturing, high-speed transmission, and new energy applications. It provides stable connections and efficient signal transmission for electronic products, promotes the development of electronic technology, and promotes sustainable development. The modern value of copper clad laminate includes: (1) With the development of communication technology, the demand for high-speed data transmission continues to grow. Copper clad laminate has good high-frequency performance and can meet the requirements of high-speed data transmission. It plays an important role in communication equipment, data centers and other fields. Copper clad laminate is widely used in the manufacture of high-speed transmission circuit boards and signal transmission media. (2) The conductivity and durability of copper clad laminate make it widely used in the power industry. As a conductive medium, copper clad laminate plays a key role in transmission lines, providing reliable current transmission and ensuring the normal operation of the power system. Its durability and stability also ensure the reliability of equipment under various environmental conditions, providing important support for the development of the power industry.

[0003] However, phenolic resin copper clad laminates also have some defects. For example, when electronic components and circuit boards are affected by excessively high temperatures, their performance and reliability will be reduced, and they may even fail. Therefore, it is necessary to improve the high temperature resistance of copper clad laminates, improve heat dissipation performance, keep the operating temperature of electronic equipment within an acceptable range, and effectively extend the service life of the equipment. In addition, copper clad laminates in electronic equipment are usually connected to circuits and electrical energy, so when a fire occurs, the flame retardant properties of copper clad laminates are particularly important. Improving flame retardancy can reduce the risk of fire and slow the spread of fire.

[0004] In order to overcome the defects of the prior art, the present invention provides an alumina filled phenolic resin copper clad laminate and a preparation method thereof. Summary of the invention

[0005] The object of the present invention is to provide an alumina filled phenolic resin copper clad laminate and a preparation method thereof, so as to solve the problems in the prior art.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0007] A method for preparing an alumina-filled phenolic resin copper-clad laminate comprises the following steps:

[0008] Step 1: Mix the formaldehyde aqueous solution, phenol and sodium hydroxide, stir and react at 85-90° C. for 4-6 hours, and continue to react for 2-3 hours after reducing the pressure to obtain a phenolic resin prepolymer; add 4-hydroxybenzenesulfonic acid dropwise to the formaldehyde aqueous solution at 0-4° C. to obtain a benzenesulfonic acid prepolymer; mix the phenolic resin prepolymer and 24 / 25 parts by weight of ethanol, and slowly stir for 3-5 hours to obtain a white emulsion; mix the benzenesulfonic acid prepolymer and 1 / 25 parts by weight of ethanol evenly, slowly dropwise add to the white emulsion, react at 75-80° C. for 4-6 hours, and after the reaction is completed, centrifuge, wash, dry and solidify to obtain phenolic resin microspheres;

[0009] Step 2: N, N-dimethylacetamide and 4-nitrophthalonitrile are mixed, stirred until dissolved, and then phenolic resin microspheres are added and the temperature is raised to 90-100° C., and then anhydrous potassium carbonate is added and stirred until completely dissolved, and the mixture is reacted at 90-100° C. for 20-24 hours. After the reaction is completed, the mixture is cooled, the pH value is adjusted, extracted, and dehydrated under reduced pressure to prepare a modified phenolic resin;

[0010] Step 3: Mix the modified phenolic resin, unsaturated polyester resin, butanone, modified alumina filler, flame retardant and photoinitiator to obtain a mixture, immerse the glass fiber cloth in the mixture, and cure it at high temperature and ultraviolet light with a wavelength of 400-410nm for 20-30min to obtain a semi-cured sheet; overlap copper foil on both sides of the semi-cured sheet, and prepare a finished product after lamination.

[0011] More optimally, in step one, the pressure after depressurization is 0.08-0.09 MPa.

[0012] More optimally, in step one, when preparing the phenolic resin prepolymer, the mass ratio of the formaldehyde aqueous solution, phenol and sodium hydroxide is 8:(6-6.5):1; when preparing the benzenesulfonic acid prepolymer, the mass ratio of 4-hydroxybenzenesulfonic acid and the formaldehyde aqueous solution is 3:(1-1.5).

[0013] More optimally, in step 1, when preparing phenolic resin microspheres, the mass ratio of phenolic resin prepolymer, benzenesulfonic acid prepolymer and ethanol is 1:1:(25-30).

[0014] More optimally, in step 2, the mass ratio of 4-nitrophthalonitrile, phenolic resin microspheres and anhydrous potassium carbonate is (2-3): 1: 0.08.

[0015] More optimally, in step three, the contents of the components of the resin glue are: by mass fraction, 35-45% modified phenolic resin, 15-20% unsaturated polyester resin, 10-15% butanone, 20-25% flame retardant, 3-5% photoinitiator, and the remainder is modified alumina filler.

[0016] More optimally, in step three, the flame retardant is ammonium phosphate; and the photoinitiator is 2,4,6-trimethylbenzoyldiphenylphosphine oxide.

[0017] More optimally, the preparation method of the modified alumina filler is: mix the alumina filler and anhydrous ethanol, ultrasonically disperse for 15-25 minutes, use acetic acid to adjust the pH to 4.5-5.0, then add silane coupling agent KH590, ultrasonically disperse for 30-40 minutes, react in a water bath at 70-80°C for 6-8 hours, and after the reaction is completed, centrifuge, wash, and dry to prepare the modified alumina filler.

[0018] More optimally, when preparing the modified alumina filler, the mass ratio of the alumina filler, anhydrous ethanol and silane coupling agent KH590 is 1:3:(0.03-0.05).

[0019] More optimally, in step three, the high temperature curing temperature is 200-220°C; the lamination molding process parameters are: temperature is 180-200°C, pressure is 2-4MPa, and time is 1-2h.

[0020] Beneficial effects of the present invention:

[0021] The present invention prepares a phenolic resin prepolymer by adding formaldehyde aqueous solution, phenol and sodium hydroxide; prepares a benzenesulfonic acid prepolymer by adding 4-hydroxybenzenesulfonic acid and formaldehyde aqueous solution; and prepares a phenolic resin microsphere by mixing the phenolic resin prepolymer, the benzenesulfonic acid prepolymer and ethanol. N, N-dimethylacetamide, 4-nitrophthalonitrile, phenolic resin microspheres and anhydrous potassium carbonate are mixed to prepare a modified phenolic resin. The modified phenolic resin, unsaturated polyester resin, butanone, modified alumina filler, flame retardant and photoinitiator are mixed to obtain a mixture, glass fiber cloth is impregnated in the mixture, and cured at high temperature and ultraviolet light to obtain a semi-cured sheet; the semi-cured sheet is overlapped with copper foil and laminated to obtain a finished product. The finished product prepared by the present invention has good flame retardancy and high temperature resistance, and therefore has broad application prospects in the technical field of copper clad laminate preparation.

[0022] The present invention is characterized in that, in step one, phenolic resin prepolymer, benzenesulfonic acid prepolymer and ethanol are mixed to prepare phenolic resin microspheres. The phenolic resin microspheres prepared by the present invention can form stable carbon microspheres after being heated, which makes up for the interstitial structure between carbon layers and can effectively block the transmission of heat, oxygen and combustible gas. In addition, the specific surface area of ​​the microspheres is large, so the contact area with the matrix is ​​large, and the cracks induced by the composite material stop when encountering the microspheres, and the microspheres can absorb the impact strength, increase the tensile strength, and improve the mechanical properties of the phenolic resin.

[0023] The present invention is characterized in that, in step 2, phenolic resin microspheres, anhydrous potassium carbonate, N, N-dimethylacetamide and 4-nitrophthalonitrile are mixed to prepare a modified phenolic resin. In this step, phenolic resin microspheres with phenolic hydroxyl groups and 4-nitrophthalonitrile containing nitrile groups undergo affinity substitution reaction to prepare a modified phenolic resin. The modified phenolic resin contains more nitrile groups, and the nitrile groups have a heat-resistant structure with strong polarity. The nitrile groups are introduced into the phenolic resin structure, which can increase the intermolecular force, increase the curing reaction temperature of the phenolic resin, and improve the high temperature resistance of the phenolic resin.

[0024] The present invention is characterized in that, in step three, a modified phenolic resin, an unsaturated polyester resin, butanone, a modified alumina filler, a flame retardant and a photoinitiator are mixed to obtain a mixture, a glass fiber cloth is impregnated in the mixture, and a semi-cured sheet is obtained by curing. The modified alumina filler is obtained by modifying the alumina filler by adding a silane coupling agent KH590. The surface properties of the filler can be changed by modifying the alumina filler, the compatibility between the filler and the resin can be enhanced, and the dispersibility and flame retardant effect thereof in the resin can be improved. In addition, in step three, the thiol groups on the surfaces of the unsaturated polyester resin and the modified alumina filler can rapidly undergo a thiol-ene click reaction under the initiation of the photoinitiator 2,4,6-trimethylbenzoyldiphenylphosphine oxide to form a cross-linked network, and the filler can react with the resin to mix in this step, and a closer bond is formed between the filler and the resin, thereby enhancing the bonding strength between the filler and the resin. This close combination can improve the mechanical properties and durability of the material. DETAILED DESCRIPTION

[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] Source of raw materials:

[0027] The formaldehyde aqueous solution was provided by Shandong Gucheng Chemical Technology Co., Ltd., model 01, and the active ingredient was 37%; the unsaturated polyester resin was provided by Hebei Jingchuang New Materials Co., Ltd., model CR-0011. In terms of mass parts, one part is 1g.

[0028] Embodiment 1: Step 1: 8 g of formaldehyde aqueous solution, 6 g of phenol and 1 g of sodium hydroxide are mixed, stirred and reacted at 90° C. for 6 h, and the pressure is reduced to 0.09 MPa and then the reaction is continued for 3 h to obtain a phenolic resin prepolymer; 3 g of 4-hydroxybenzenesulfonic acid is added dropwise to 1 g of formaldehyde aqueous solution at 4° C. to obtain a benzenesulfonic acid prepolymer; 1 g of the phenolic resin prepolymer is mixed with 24 g of ethanol and slowly stirred for 5 h to obtain a white emulsion; 1 g of the benzenesulfonic acid prepolymer and 1 g of ethanol are evenly mixed, slowly added dropwise to the white emulsion, and reacted at 80° C. for 6 h. After the reaction is completed, the phenolic resin microspheres are obtained by centrifugation, washing, drying and curing;

[0029] Step 2: 4 g of N, N-dimethylacetamide and 2 g of 4-nitrophthalonitrile were mixed and stirred until dissolved, and then 1 g of phenolic resin microspheres were added and the temperature was raised to 100° C., and then 0.08 g of anhydrous potassium carbonate was added and stirred until completely dissolved, and the mixture was reacted at 100° C. for 24 h. After the reaction was completed, the mixture was cooled, the pH was adjusted, extracted, and dehydrated under reduced pressure to prepare a modified phenolic resin;

[0030] Step 3: 1 g of alumina filler and 3 g of anhydrous ethanol were mixed, ultrasonically dispersed for 25 min, acetic acid was used to adjust the pH to 5.0, and then 0.03 g of silane coupling agent KH590 was added, ultrasonically dispersed for 40 min, and reacted in a water bath at 80° C. for 8 h. After the reaction was completed, the modified alumina filler was prepared by centrifugation, washing, and drying;

[0031] Step 4: In terms of mass fraction, 35% of modified phenolic resin, 15% of unsaturated polyester resin, 12% of butanone, 23% of modified alumina filler, 10% of ammonium phosphate and 5% of 2,4,6-trimethylbenzoyldiphenylphosphine oxide are mixed to obtain a mixture, the glass fiber cloth is impregnated in the mixture, and the mixture is cured at a high temperature of 220° C. and a wavelength of 410 nm under ultraviolet light for 30 minutes to obtain a semi-cured sheet; copper foil is overlapped on both sides of the semi-cured sheet, and the finished product is prepared after lamination at a temperature of 200° C. and a pressure of 4 MPa for 2 hours.

[0032] Example 2: Step 1: 8 g of formaldehyde aqueous solution, 6 g of phenol and 1 g of sodium hydroxide were mixed, stirred and reacted at 87° C. for 5 h, and the pressure was reduced to 0.085 MPa and the reaction was continued for 2.5 h to obtain a phenolic resin prepolymer; 3 g of 4-hydroxybenzenesulfonic acid was added dropwise to 1 g of formaldehyde aqueous solution at 2° C. to obtain a benzenesulfonic acid prepolymer; 1 g of the phenolic resin prepolymer was mixed with 24 g of ethanol and slowly stirred for 4 h to obtain a white emulsion; 1 g of the benzenesulfonic acid prepolymer and 1 g of ethanol were evenly mixed, slowly added dropwise to the white emulsion, and reacted at 77° C. for 5 h. After the reaction was completed, the phenolic resin microspheres were obtained by centrifugation, washing, drying and curing;

[0033] Step 2: 4 g of N, N-dimethylacetamide and 2 g of 4-nitrophthalonitrile were mixed and stirred until dissolved, and then 1 g of phenolic resin microspheres were added and the temperature was raised to 95° C., and then 0.08 g of anhydrous potassium carbonate was added and stirred until completely dissolved, and the mixture was reacted at 95° C. for 22 h. After the reaction was completed, the mixture was cooled, the pH was adjusted, extracted, and dehydrated under reduced pressure to prepare a modified phenolic resin;

[0034] Step 3: 1 g of alumina filler and 3 g of anhydrous ethanol were mixed, ultrasonically dispersed for 20 min, acetic acid was used to adjust the pH to 4.7, and then 0.03 g of silane coupling agent KH590 was added, ultrasonically dispersed for 35 min, and reacted in a 75°C water bath for 7 h. After the reaction was completed, the modified alumina filler was prepared by centrifugation, washing, and drying;

[0035] Step 4: In terms of mass fraction, 35% of modified phenolic resin, 15% of unsaturated polyester resin, 12% of butanone, 23% of modified alumina filler, 10% of ammonium phosphate and 5% of 2,4,6-trimethylbenzoyldiphenylphosphine oxide are mixed to obtain a mixture, the glass fiber cloth is impregnated in the mixture, and the mixture is cured at a high temperature of 215° C. and a wavelength of 405 nm under ultraviolet light for 25 minutes to obtain a semi-cured sheet; copper foil is overlapped on both sides of the semi-cured sheet, and the finished product is prepared after lamination at a temperature of 190° C. and a pressure of 3 MPa for 1.5 hours.

[0036] Example 3: Step 1: 8 g of formaldehyde aqueous solution, 6 g of phenol and 1 g of sodium hydroxide were mixed, stirred and reacted at 85° C. for 4 h, and the pressure was reduced to 0.08 MPa and then continued to react for 2 h to obtain a phenolic resin prepolymer; 3 g of 4-hydroxybenzenesulfonic acid was added dropwise to 1 g of formaldehyde aqueous solution at 0° C. to obtain a benzenesulfonic acid prepolymer; 1 g of the phenolic resin prepolymer was mixed with 24 g of ethanol and slowly stirred for 3 h to obtain a white emulsion; 1 g of the benzenesulfonic acid prepolymer and 1 g of ethanol were evenly mixed, slowly added dropwise to the white emulsion, and reacted at 75° C. for 4 h. After the reaction was completed, the mixture was centrifuged, washed, dried, and solidified to obtain phenolic resin microspheres;

[0037] Step 2: 4 g of N, N-dimethylacetamide and 2 g of 4-nitrophthalonitrile were mixed and stirred until dissolved, and then 1 g of phenolic resin microspheres were added and the temperature was raised to 90° C., and then 0.08 g of anhydrous potassium carbonate was added and stirred until completely dissolved, and the mixture was reacted at 90° C. for 20 h. After the reaction was completed, the mixture was cooled, the pH was adjusted, extracted, and dehydrated under reduced pressure to prepare a modified phenolic resin;

[0038] Step 3: 1 g of alumina filler and 3 g of anhydrous ethanol were mixed, ultrasonically dispersed for 15 min, acetic acid was used to adjust the pH to 4.5, and then 0.03 g of silane coupling agent KH590 was added, ultrasonically dispersed for 30 min, and reacted in a 70° C. water bath for 6 h. After the reaction was completed, the modified alumina filler was prepared by centrifugation, washing, and drying;

[0039] Step 4: In terms of mass fraction, 35% of modified phenolic resin, 15% of unsaturated polyester resin, 12% of butanone, 23% of modified alumina filler, 10% of ammonium phosphate and 5% of 2,4,6-trimethylbenzoyldiphenylphosphine oxide are mixed to obtain a mixture, the glass fiber cloth is impregnated in the mixture, and the mixture is cured at a high temperature of 200° C. and a wavelength of 400 nm under ultraviolet light for 20 minutes to obtain a semi-cured sheet; copper foil is overlapped on both sides of the semi-cured sheet, and the finished product is prepared after lamination at a temperature of 180° C. and a pressure of 2 MPa for 1 hour.

[0040] Comparative Example 1: The preparation step of the modified phenolic resin is removed, and the rest is the same as Example 1, and the specific steps are as follows: Step 1: 8g of formaldehyde aqueous solution, 6g of phenol and 1g of sodium hydroxide are mixed, stirred and reacted at 90°C for 6h, and the pressure is reduced to 0.09MPa and the reaction is continued for 3h to obtain a phenolic resin prepolymer; 3g of 4-hydroxybenzenesulfonic acid is added dropwise to 1g of formaldehyde aqueous solution at 4°C to obtain a benzenesulfonic acid prepolymer; 1g of the phenolic resin prepolymer and 24g of ethanol are mixed and slowly stirred for 5h to obtain a white emulsion; 1g of the benzenesulfonic acid prepolymer and 1g of ethanol are mixed evenly, slowly added dropwise to the white emulsion, and reacted at 80°C for 6h. After the reaction is completed, the phenolic resin microspheres are obtained by centrifugation, washing, drying and curing;

[0041] Step 2: 1 g of alumina filler and 3 g of anhydrous ethanol were mixed, ultrasonically dispersed for 25 min, acetic acid was used to adjust the pH to 5.0, and then 0.03 g of silane coupling agent KH590 was added, ultrasonically dispersed for 40 min, and reacted in a water bath at 80° C. for 8 h. After the reaction was completed, the mixture was centrifuged, washed, and dried to prepare a modified alumina filler;

[0042] Step 3: In terms of mass fraction, 35% phenolic resin microspheres, 15% unsaturated polyester resin, 12% butanone, 23% modified alumina filler, 10% ammonium phosphate and 5% 2,4,6-trimethylbenzoyldiphenylphosphine oxide are mixed to obtain a mixture, the glass fiber cloth is impregnated in the mixture, and the mixture is cured at a high temperature of 200° C. and a wavelength of 400 nm under ultraviolet light for 20 minutes to obtain a semi-cured sheet; copper foil is overlapped on both sides of the semi-cured sheet, and the finished product is prepared after lamination at a temperature of 200° C. and a pressure of 4 MPa for 2 hours.

[0043] Comparative Example 2: The preparation step of the modified alumina filler is removed, and the rest is the same as Example 1, and the specific steps are as follows: Step 1: 8g of formaldehyde aqueous solution, 6g of phenol and 1g of sodium hydroxide are mixed, stirred and reacted at 90°C for 6h, and the pressure is reduced to 0.09MPa and the reaction is continued for 3h to obtain a phenolic resin prepolymer; 3g of 4-hydroxybenzenesulfonic acid is added dropwise to 1g of formaldehyde aqueous solution at 4°C to obtain a benzenesulfonic acid prepolymer; 1g of the phenolic resin prepolymer and 24g of ethanol are mixed and slowly stirred for 5h to obtain a white emulsion; 1g of the benzenesulfonic acid prepolymer and 1g of ethanol are mixed evenly, slowly added dropwise to the white emulsion, and reacted at 80°C for 6h. After the reaction is completed, centrifugation, washing, drying and curing are performed to obtain phenolic resin microspheres;

[0044] Step 2: 4 g of N, N-dimethylacetamide and 2 g of 4-nitrophthalonitrile were mixed and stirred until dissolved, and then 1 g of phenolic resin microspheres were added and the temperature was raised to 100° C., and then 0.08 g of anhydrous potassium carbonate was added and stirred until completely dissolved, and the mixture was reacted at 100° C. for 24 h. After the reaction was completed, the mixture was cooled, the pH was adjusted, extracted, and dehydrated under reduced pressure to prepare a modified phenolic resin;

[0045] Step 3: In terms of mass fraction, 35% of modified phenolic resin, 15% of unsaturated polyester resin, 12% of butanone, 23% of aluminum oxide filler, 10% of ammonium phosphate and 5% of 2,4,6-trimethylbenzoyldiphenylphosphine oxide are mixed to obtain a mixture, the glass fiber cloth is impregnated in the mixture, and the mixture is cured at a high temperature of 200° C. and a wavelength of 400 nm under ultraviolet light for 20 minutes to obtain a semi-cured sheet; copper foil is overlapped on both sides of the semi-cured sheet, and the finished product is prepared after lamination at a temperature of 200° C. and a pressure of 4 MPa for 2 hours.

[0046] Detection test:

[0047] High temperature resistance test: The prepreg prepared by the present invention is used as a sample, and the sample is placed at a high temperature of 500° C. for 6 hours, and the shedding condition of the sample surface is observed to determine the high temperature resistance performance.

[0048] Tensile strength test: The mixture prepared in step 4 of the embodiment of the present invention is cured at a high temperature of 200°C and a wavelength of 400nm under ultraviolet light for 20 minutes to obtain a sample. According to GB / T 1040-1992 "Plastic Tensile Properties Test Method", the size of the sample is cut to 115×25×2mm, the experimental tensile speed is 50mm / min±10%, three points are measured for each sample, the arithmetic mean is taken, and finally the tensile strength is calculated by the formula.

[0049] Oxygen index performance test: The mixture prepared in step 4 of the embodiment of the present invention is cured at high temperature of 200°C and ultraviolet light with a wavelength of 400nm for 20 minutes to obtain a sample. According to the GB / T 2406.2-2009 standard, the size of the sample is cut to 70×7×3mm, the initial oxygen concentration is 21%, and a mixed gas of oxygen and nitrogen is introduced at a flow rate of 40mm / s in a 25°C environment. Then, the oxygen index is calculated using the formula. The larger the oxygen index, the better the flame retardant performance. The results are as follows:

[0050] Surface condition Oxygen index / % Tensile strength / MPa Example 1 The surface is slightly deformed, but not falling off 35 48.5 Example 2 The surface is slightly deformed, but not falling off 34 48.4 Example 3 The surface is slightly deformed, but not falling off 34 48.4 Comparative Example 1 The surface is greatly deformed, resulting in large-scale shedding 35 48.0 Comparative Example 2 The surface is slightly deformed, but not falling off 31 48.2

[0051] Conclusion: The dosage of Examples 1 to 3 remains unchanged, and only some reaction parameters are modified. It can be seen from the experimental data that there is no obvious fluctuation in the various properties of the sample. Comparative Example 1: The preparation step of the modified phenolic resin is removed, and the rest is the same as Example 1. It can be seen from the experimental data that compared with Example 1, the surface of the semi-cured sheet has a large deformation and a large area of ​​​​falling off, and the tensile strength is reduced to 48.0MPa. The reason for analysis is: the phenolic resin microspheres are modified by adding 4-nitrophthalonitrile to obtain a modified phenolic resin. The high temperature resistance of the phenolic resin can be effectively improved by introducing a nitrile group. Therefore, after the modification step is removed, the surface of the semi-cured sheet has a large deformation and a large area of ​​​​falling off; in addition, since 4-nitrophthalonitrile also contains a certain amount of benzene rings, it will affect the mechanical properties of the resin after removal, and the tensile strength is reduced.

[0052] Comparative Example 2: The preparation step of the modified alumina filler is removed, and the rest is the same as Example 1. It can be seen from the experimental data that compared with Example 1, the oxygen index is reduced to 31%, and the tensile strength is reduced to 48.2 MPa. The reason is analyzed as follows: the alumina filler is modified by adding silane coupling agent KH590 to obtain a modified alumina filler. The modification can improve the dispersibility of the original alumina filler, reduce agglomeration, and enhance the overall performance of the alumina filler, thereby improving the flame retardant properties and mechanical properties of the resin; therefore, the preparation step of the modified alumina filler is removed, and the oxygen index and tensile strength of the sample are reduced.

[0053] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process method article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process method article or device.

[0054] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing an alumina-filled phenolic resin copper-clad laminate, characterized in that: The following steps are involved: Step 1: Mix the formaldehyde aqueous solution, phenol and sodium hydroxide, stir and react at 85-90° C. for 4-6 hours, and continue to react for 2-3 hours after reducing the pressure to obtain a phenolic resin prepolymer; add 4-hydroxybenzenesulfonic acid dropwise to the formaldehyde aqueous solution at 0-4° C. to obtain a benzenesulfonic acid prepolymer; mix the phenolic resin prepolymer and 24 / 25 parts by weight of ethanol, and slowly stir for 3-5 hours to obtain a white emulsion; mix the benzenesulfonic acid prepolymer and 1 / 25 parts by weight of ethanol evenly, slowly dropwise add to the white emulsion, react at 75-80° C. for 4-6 hours, and after the reaction is completed, centrifuge, wash, dry and solidify to obtain phenolic resin microspheres; Step 2: N, N-dimethylacetamide and 4-nitrophthalonitrile are mixed, stirred until dissolved, and then phenolic resin microspheres are added and the temperature is raised to 90-100° C., and then anhydrous potassium carbonate is added and stirred until completely dissolved, and the mixture is reacted at 90-100° C. for 20-24 hours. After the reaction is completed, the mixture is cooled, the pH value is adjusted, extracted, and dehydrated under reduced pressure to prepare a modified phenolic resin; Step 3: Mix the modified phenolic resin, unsaturated polyester resin, butanone, modified alumina filler, flame retardant and photoinitiator to obtain a mixture, immerse the glass fiber cloth in the mixture, and cure it at high temperature and ultraviolet light with a wavelength of 400-410nm for 20-30min to obtain a semi-cured sheet; overlap copper foil on both sides of the semi-cured sheet, and prepare a finished product after lamination.

2. The method for preparing an alumina-filled phenolic resin copper-clad laminate according to claim 1, characterized in that: In step 1, the pressure after decompression is 0.08-0.09MPa.

3. The method for preparing an alumina-filled phenolic resin copper-clad laminate according to claim 1, characterized in that: In step 1, when preparing the phenolic resin prepolymer, the mass ratio of the formaldehyde aqueous solution, phenol and sodium hydroxide is 8: (6-6.5): 1; when preparing the benzenesulfonic acid prepolymer, the mass ratio of 4-hydroxybenzenesulfonic acid and the formaldehyde aqueous solution is 3: (1-1.5).

4. The method for preparing an alumina-filled phenolic resin copper-clad laminate according to claim 1, characterized in that: In step 1, when preparing phenolic resin microspheres, the mass ratio of phenolic resin prepolymer, benzenesulfonic acid prepolymer and ethanol is 1:1:(25-30).

5. The method for preparing an alumina filled phenolic resin copper clad laminate according to claim 1, characterized in that: In step 2, the mass ratio of 4-nitrophthalonitrile, phenolic resin microspheres and anhydrous potassium carbonate is (2-3): 1: 0.

08.

6. The method for preparing an alumina-filled phenolic resin copper-clad laminate according to claim 1, characterized in that: In step three, the contents of the components of the resin glue are: by mass fraction, 35-45% modified phenolic resin, 15-20% unsaturated polyester resin, 10-15% butanone, 20-25% flame retardant, 3-5% photoinitiator, and the remainder is modified alumina filler.

7. The method for preparing an alumina-filled phenolic resin copper-clad laminate according to claim 1, characterized in that: In step three, the flame retardant is ammonium phosphate; and the photoinitiator is 2,4,6-trimethylbenzoyldiphenylphosphine oxide.

8. The method for preparing an alumina filled phenolic resin copper clad laminate according to claim 6, characterized in that: The preparation method of the modified alumina filler is as follows: the alumina filler and anhydrous ethanol are mixed, ultrasonically dispersed for 15-25 minutes, acetic acid is used to adjust the pH to 4.5-5.0, and then a silane coupling agent KH590 is added, ultrasonically dispersed for 30-40 minutes, reacted in a water bath at 70-80°C for 6-8 hours, and after the reaction is completed, the modified alumina filler is prepared by centrifugation, washing, and drying.

9. The method for preparing an alumina-filled phenolic resin copper-clad laminate according to claim 8, characterized in that: When preparing the modified alumina filler, the mass ratio of the alumina filler, anhydrous ethanol and the silane coupling agent KH590 is 1:3:(0.03-0.05).

10. The method for preparing an alumina filled phenolic resin copper clad laminate according to claim 1, characterized in that: In step three, the high temperature curing temperature is 200-220°C; the lamination molding process parameters are: temperature is 180-200°C, pressure is 2-4MPa, and time is 1-2h.

Citation Information

Patent Citations

  • Alumina-filled phenolic resin-based flame-retardant copper-clad plate and preparation method thereof

    CN118288634A

  • Phenolic resin composite plastic and preparation method therefor

    WO2023123227A1